Rethinking Infrastructure Across the Humanities - Pinnix, Aaron; Volmar, Axel; Esposito, Fernando; Binder, Nora (Edition Kulturwissenschaft, 2023)
Infrastructure comprises a combination of sociotechnical, political, and cultural arrangements that provide resources and services. The contributors to this volume show, in their respective fields, how infrastructures are both generative forces and the materialized products of quotidian practices that affect and guide people's lives. Organized via shared conceptual foci, this volume demonstrates infrastructuralist perspectives as an important transdisciplinary approach within the humanities.